Analisis Deskriptif Hadis tentang Halal Food - Salsabilla Desviani Putri (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss halal and haram in food from the perspective of hadith. This research method uses a qualitative type through literature study by applying content analysis. The results and discussion of this study include general views of halal and haram, hadith about halal and haram, and how to distinguish halal and haram food. The conclusion of this study shows that in Islam halal food is food that is allowed to be done, used, or cultivated and free from various things that are harmful or prohibited. While haram food is not allowed or prohibited to be used for food ingredients that are prohibited to be carried out or used either because of the substance in it or how to get it.